Man and the Arctic Environment: Parameters of Reciprocal Influence - BELONOZHKO, Marina L.; BARBAKOV, Oleg M.; GABISHEVA, Lyudmila K. (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018DO - 10.14505//jemt.v9.5(29).07, 2018)
The paper deals with the analysis of specific parameters of reciprocal influence between man and the Arctic environment, the formulation of the theoretic provisions, as well as the development of the scientific conclusions regarding the definition of the perspectives and peculiarities of the Arctic Region environmental development under conditions of globalization and the world environmental crisis. As the results of the conducted research, the authors revealed and generalized the scientific approaches towards the definition of the legal status of the Arctic; stated the legal contents and the meaning of the basic environmental standards and programs of the international legislation regarding the Arctic Region; considered the spheres of influence of the states on the Arctic territory and on the environmental situation of this region in general; characterized the environmental conditions for living of the Arctic population; and defined the nature of the adverse anthropogenic effect on the environment of the investigated region. The analysis of the literature helped to formulate the theoretical conclusions, to develop the practical recommendations and to forecast the long-run perspectives and peculiarities of the Arctic environmental development. It is substantiated that the reciprocal influence between man and the environment in the territory of the Arctic Region moves towards a qualitatively new stage, which forces the states to adopt the strategical decisions in the sphere of the reclamation of the Arctic Region only considering the preservation of the ecosystem, provision of the proper living quality of the Arctic population, as well as the environmentalization of all the kinds of economic activities in the region. The paper contains the scientific substantiation and proposes the development of the Concept of Sustainable Development and Preservation of the Ecosystem for the Arctic Region, which will also include the monitoring system for the condition of the Arctic.